Candida albicans Targets a Lipid Raft/Dectin-1 Platform to Enter Human Monocytes and Induce Antigen Specific T Cell Responses - de Turris, Valeria (PLoS One, 2015)
Several pathogens have been described to enter host cells via cholesterol-enriched membrane lipid raft microdomains. We found that disruption of lipid rafts by the cholesterol-extracting agent methyl-β-cyclodextrin or by the cholesterol-binding antifungal drug Amphotericin B strongly impairs the uptake of the fungal pathogen Candida albicans by human monocytes, suggesting a role of raft microdomains in the phagocytosis of the fungus. Time lapse confocal imaging indicated that Dectin-1, the C-type lectin receptor that recognizes Candida albicans cell wall-associated β-glucan, is recruited to lipid rafts upon Candida albicans uptake by monocytes, supporting the notion that lipid rafts act as an entry platform. Interestingly disruption of lipid raft integrity and interference with fungus uptake do not alter cytokine production by monocytes in response to Candida albicans but drastically dampen fungus specific T cell response. In conclusion, these data suggest that monocyte lipid rafts play a crucial role in the innate and adaptive immune responses to Candida albicans in humans and highlight a new and unexpected immunomodulatory function of the antifungal drug Amphotericin B.